Elements on contrast in nathaniel hawthorne´s the scarlet letter - Castillo Castillo, Gabriela; Jaramillo Ortiz, Freddy
Elements of Contrast in Nathaniel Hawthorne?s, The Scarlet Letter,? is a work, which indicates different aspects of the novel itself. In the first place, we analyzed the type of novel to show that it is not just a Romance story but a Historical one as well. Aside from this, it has extraordinary elements that make it really interesting and amazing. Moreover, each contrast shows how skillful Hawthorne was with every detail. Another topic developed is the different moral beliefs that existed within Puritanism as well as Hawthorne?s own thoughts and ideas. Puritans had different rules that made their town appear, to themselves, unique and blessed. Their religion was linked to their politics and laws because they wanted to create a life where they could avoid everything they did not like from the Old World. Additionally, the entire story is focused on the Puritan treatment of females, including the changes Hester undergoes during the novel; the Puritan women versus the modern women; the way Hawthorne?s thoughts about women, and the different conceptions of love and sex according to Puritans in contrast to those of modern people. Perhaps the reason Nathaniel Hawthorne presented new ideas about women was that he was surrounded by females; and he admired them and saw them in a totally different way the way they were thought of before his time. In conclusion, The Scarlet Letter can be considered a Historical Romance novel, which among other aspects, gives the reader an idea of how hard Puritan times, was.